Chemical Oxidation of Porous Silicon in Alcohol-Lye Solutions. (14th March 2015) - Loni, A.; Batchelor, L.; Caffull, E.; Canham, L. T.
Abstract : Porous silicon membranes formed by anodization and electrochemical detachment from the parent wafers are rapidly oxidized at room temperature by immersion in lye solutions comprising methanol and sodium hydroxide (< 0.1 M). Coverage of the silicon skeleton by an oxide, the thickness of which depends on immersion time, lye concentration and alcoholic ratio, is evinced by reductions in surface area, pore volume and size, together with a color change and a susceptibility to etching in dilute hydrofluoric acid. High-porosity membranes can be almost completely converted to white mesoporous silica after immersion times of only a few minutes. Controlled oxidation and hydrofluoric acid etching is used to significantly enlarge the pores.